Identification of Cotton F1 Hybrids and their Parents through Molecular Marker under Salinity Stress - Vekariya, V. K.; Singh, Diwakar; Rajkumar; Faldu, G. O. (International Journal of Bio-resource and Stress Management, 2021)
An experiment was carried out at Main Cotton Research Station, NAU, Surat, Gujarat, India during 2018–2020 to identify F1 hybrids and their parents through SSR marker for salinity tolerance in cotton. The four cotton parents (two salt tolerant and two salt sensitive) were crossed in a diallel fashion to obtain twelve cotton hybrids and subjected to DNA isolation and PCR amplification with SSR markers. In the present study, six SSR markers (TMB0409, DPL0094, BNL686, JESPR153, CM45 and MGHES006) were identified to be polymorphic between parents and the hybrids. The SSR primer TMB0409, DPL0094, JESPR153 and CM45 identified two fragments each from different parents in two, two, four and eight cotton hybrids, respectively, which confirmed true hybrids. Hence, the SSR molecular marker, individually or in combination can be used to distinguish and confirm the hybrid and parents in cotton with special reference to salinity. The PCA analysis revealed that BNL686–1 (248 bp) allele contributed significantly to the quantum of variation as explained by PC1. Hence, this allele is able to serve as a benchmark for ascertaining the efficient pattern of grouping between genotypes. Further, the marker CM45 amplified a fragment specific to the saline tolerant parents which was absent in sensitive parents as well as a fragment produced in sensitive parent which was absent in the tolerant parents, hence the molecular marker CM45 may associate with the salinity tolerance in cotton and can be used for salinity tolerant breeding program after confirming in a large population.